Experimental Analysis of Forces During Take-Off of Birds - Barata, Jorge M M (2019)
Copyright © 2017 by Jorge M. M. Barata, Telmo J. A. Silva, Fernando M. S. P. Neves and André R. R. Silva. Published by the American Institute of Aeronautics and Astronautics, Inc., with permission.